The Tension between work and homelife - Mejía Madrid, Renato (2014)
In this paper, the author presents the problem that thetension between work and family life represent. in that way, a gender perspective is used to analyze masculine and feminine roles in different work environments, and compare them with labor policies. the author concludes emphasizing the insufficiency of the actual policies, and then he suggests corresponsibility as a solution.